MPL W515 L/K mutations in myeloproliferative neoplasms - Sohaila Eldeweny; Hosny Ibrahim; Ghada Elsayed; Mohamed Samra (Egyptian Journal of Medical Human Genetics, 2019)
Abstract Background Myeloproliferative neoplasms (MPNs) describe a group of diseases involving the bone marrow (BM). Classical MPNs are classified into chronic myelogenous leukemia (CML), polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). This classification is based on the presence of Philadelphia (Ph) chromosome (BCR/ABL1). CML is BCR/ABL1-positive while PV, ET, and PMF are negative. JAK2 p. Val617Phe pathological variant is the most associated mutation in BCR/ABL1-negative MPNs. The frequency of JAK2 p. Val617Phe is 90–95% in PV patients, 50–60% in ET, and 40–50% in patients with PMF. Studies on MPL gene led to the revelation of a gain of function pathological variants in JAK2 p. Val617Phe-negative myeloproliferative neoplasms (MPNs). MPL p. W515 L/K pathological variants are the most common across all mutations in MPL gene. The prevalence of these pathological variants over the Egyptian population is not clear enough. In the present study, we aimed to investigate the prevalence of MPL p. W515 L/K pathological variants in the Philadelphia (Ph)-negative MPNs over the Egyptian population. Results We have tested 60 patients with Ph-negative MPNs for MPL p. W515 L/K pathological variants. Median age was 51 (22–73) years. No MPL p. W515 L/K pathological variants were detected among our patients. JAK2 p. Val617Phe in PV and PMF patients showed significantly lower frequency than other studies. Splenomegaly was significantly higher in ET patients compared to other studies. Conclusion MPL p. W515 L/K pathological variants are rare across the Egyptian Ph-negative MPNs, and further studies on a large number are recommended. MPN patients in Egypt are younger compared to different ethnic groups.